Viral Strategies and Cellular Countermeasures That Regulate mRNA Access to the Translation Apparatus - Christopher U. T. Hellen (Viruses, 2025)
The papers introduced in the Commentary present new insights and review aspects of current knowledge concerning the competition between viruses and their hosts for the cellular translation apparatus. Viruses depend on this apparatus and utilize diverse mechanisms to usurp it for the translation of viral mRNAs and to suppress synthesis of cellular proteins. Virus-induced modification of translation factors, selective abrogation of mRNA binding to ribosomes and degradation of cellular mRNAs all impair elements of the innate immune response, thereby undermining host defenses against infection. Various cellular mechanisms prevent translation of viral mRNAs, by modifying components of the translation apparatus to effect a generalized shut-off of translation or by binding of host proteins to viral mRNAs to induce their degradation or to prevent their engagement with the translation apparatus. Viruses have in turn evolved countermeasures to evade these defenses, for example by encoding proteins that impair the activity of host factors or via alterations in the sequence and structure of viral mRNAs. Such changes enable viral mRNAs to avoid recognition by host factors or to support translation initiation by specialized mechanisms that involve only a subset of the factors that are required by cellular mRNAs.